Specialized dendritic cells induce tumor-promoting IL-10+IL-17+ FoxP3 neg regulatory CD4+ T cells in pancreatic carcinoma - Rocky M. Barilla (Nature Portfolio, 2019)
Pancreatic ductal adenocarcinoma is characterized by a highly immunosuppressive tumour microenvironment. Here, the authors show that specialized subsets of tumour-infiltrating dendritic cells induce distinct CD4+ T cell programs and specifically identify a CD103–CD11b+ subset which induces tumor-promoting FoxP3– Type-1 regulatory T cells.